Client satisfaction among people living with HIV attending an anti-retroviral therapy center with special emphasis on the sexual minority population at a teaching institution in West Bengal: A mixed-method study - Ishita Sarkar; Rahul Biswas; Sanghamitra Maulik; Ananya Ramanandi; Ankit Das; Debjani Guchhait (Journal of Family Medicine and Primary Care)
Context: Patient satisfaction is a crucial indicator of service quality in the healthcare system. There is limited information regarding the level of satisfaction of sexual minority groups of people living with HIV (PLHIV) regarding treatment services. Aims: This comparative study assessed client satisfaction among general (male and female) patients and the sexual minority group with the antiretroviral service delivery at the ART center. Settings and Design: This cross-sectional analytical study of a mixed-method approach was conducted from September 2023 to May 2024 at the ART center of Barasat Government Medical College and Hospital. Materials and Methods: A total of 430 patients were enrolled in this study. Data were collected using a face-to-face exit interview and focus group discussion. Statistical Analysis Used: Overall patient satisfaction was determined by obtaining the average scores from Likert scale responses. A Chi-square or Fisher’s exact test was used to explore associations between overall patient satisfaction and demographic characteristics of participants and other variables. A P value of 0.05 or less was considered statistically significant. Results: Overall patient satisfaction was 85.1% in general patients and 75.2% in sexual minority patients, which was a statistically significant difference between the two groups (Z test of proportion). Factors that showed significant association with satisfaction were marital status, education level, type of family, socioeconomic status, convenient service hours, and waiting time. Key areas of dissatisfaction reported in interviews and FGDs were lack of toilet facility, long waiting time, lack of space at ART center, disclosure of sexual identity of sexual minority patients, etc. Conclusions: Overall patient satisfaction was high among the study subjects though higher among general patients compared to sexual minority patients. Marital status, educational status, social class, service hours, and waiting time were found to be important predictors of patient satisfaction. The provision of increased space in the ART center and toilet facility and implementation of regular induction and refresher training for health care personnel may go a long way in further enhancement of patient satisfaction among both groups.